Palladium nanoparticles on β-cyclodextrin functionalised graphene nanosheets: a supramolecular based heterogeneous catalyst for C–C coupling reactions under green reaction conditions. Issue 9 (23rd December 2014) - Putta, Chandrababu; Sharavath, Vittal; Sarkar, Suprabhat; Ghosh, Sutapa
Abstract : Palladium nanoparticles on β-cyclodextrin functionalised graphene based supramolecular heterogeneous catalyst are used for Suzuki–Miyaura and Heck–Mizoroki coupling reactions under green reaction conditions. Abstract : The use of functional properties of native cyclodextrins in palladium nanoparticle–β-cyclodextrin–graphene nanosheet (Pd@CD–GNS) catalyzed carbon–carbon (C–C) coupling reactions have been investigated under green reaction conditions. The supramolecular catalyst was prepared by deposition of Pd nanoparticles (Pd NPs) on CD–GNS using ethanol as the greener solvent and in situ reducing agent. The catalyst was characterised by FTIR, XRD, RAMAN, UV-Vis spectroscopy, TEM, SAED, XPS and ICP-AES. The catalytic activity of these catalysts is investigated in C–C coupling reactions such as Suzuki–Miyaura and Heck–Mizoroki reactions of aryl bromides and aryl chlorides containing functional groups under green reaction conditions i.e. in water, under phosphine free and aerobic conditions. This catalyst afforded excellent selectivities for the products in good to excellent yields under low Pd loadings (0.2–0.05 mol%), while ensuring the recovery and reusability of the catalysts. The reused catalyst was characterized by FTIR, TEM, XPS and ICP-AES. The CD supramolecular mediators loaded on GNS act as stabilising agents for the Pd NPs. The excellent catalytic activity of this system was attributed to the presence of CDs, excellent dispersibility in water, hydrophobic nature of the GNS support for the accumulation of organic substrates in water, "Breslow effect", the presence of PTC to overcome the mass transfer limitation onto the surface of GNS and formation of ternary CD/substrate/additive complexes on the Pd–GNS surface.